2021
DOI: 10.3390/nu13030938
|View full text |Cite
|
Sign up to set email alerts
|

Impact of 2′-Fucosyllactose on Gut Microbiota Composition in Adults with Chronic Gastrointestinal Conditions: Batch Culture Fermentation Model and Pilot Clinical Trial Findings

Abstract: Intestinal dysbiosis has been described in patients with certain gastrointestinal conditions including irritable bowel syndrome (IBS) and ulcerative colitis. 2′-fucosyllactose (2′-FL), a prebiotic human milk oligosaccharide, is considered bifidogenic and butyrogenic. To assess prebiotic effects of 2′-FL, alone or in combination with probiotic strains (potential synbiotics), in vitro experiments were conducted on stool from healthy, IBS, and ulcerative colitis adult donors. In anaerobic batch culture fermenters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 98 publications
(112 reference statements)
2
23
0
Order By: Relevance
“…Supplementation of prebiotics as food ingredients has been proposed to prevent several inflammatory diseases [23][24][25][26][27] as well as allergies [10,28,29,30,31,32]. Cohort studies have indicated that one of the factors preceding the development of food allergies is gut dysbiosis [2,33,34].…”
Section: Introductionmentioning
confidence: 99%
“…Supplementation of prebiotics as food ingredients has been proposed to prevent several inflammatory diseases [23][24][25][26][27] as well as allergies [10,28,29,30,31,32]. Cohort studies have indicated that one of the factors preceding the development of food allergies is gut dysbiosis [2,33,34].…”
Section: Introductionmentioning
confidence: 99%
“…infantis fucosidases mentioned above can open a new perspective towards the synthesis of novel fucosylated conjugates by using different substrates beyond lactose for synthetizing 2 -fucosyllactose. This vision is oriented towards the supply those novel fucosylated conjugates to adults in combination with fucosidase producer bifidobacteria in order to maintain a healthy microbiota or to reestablish it from dysbiosis states as described previously [50,51]. In this regard, it would be important to elucidate phylogenetically, as well as structurally and physicochemically, the fucosidases of many other gut microorganism genera, as for instance Lactobacillus, Bacteroides, and Akkermansia, with the aim to reveal the whole gut fucosidase interaction.…”
Section: Discussionmentioning
confidence: 99%
“…infantis fucosidases mentioned above can open a new perspective towards the synthesis of novel fucosylated conjugates by using different substrates beyond the lactose for synthetizing 2'-fucosyllactose. This vision is oriented towards the supply those novel fucosylated conjugates to adults in combination with fucosidase producer bifidobacteria in order to maintain a healthy microbiota or to reestablish it from dysbiosis states as described previously [40,41]. In this regard, it would be important to elucidate phylogenetically as well as structurally and physicochemically the fucosidases of many other gut microorganism genus as for instance Lactobacillus, Bacteroides, and Akkermansia with the aim to reveal the whole gut fucosidases interaction.…”
Section: Discussionmentioning
confidence: 99%